Five new species of genus Encarsia Förster from China (Hymenoptera: Aphelinidae) - Geng, Hui; Li, Cheng-De (Zootaxa, 2016)
Five new species of Encarsia Förster, E. dianensis sp. nov., E. hayati sp. nov., E. biseta sp. nov., E. huangi sp. nov., and E. yunnana sp. nov. are described from China. All share a clear asetose area around the stigmal vein of the fore wing, and a key to the Chinese species of Encarsia having such a fore wing area is given based on females. Photomicrographs are provided to illustrate morphological characters of the new species.